PSII-21 The Effects of Lactobacillus Fermentum on Nursery Pig Performance - Knapp, Josh K (J Anim Sci, 2021)
The use of probiotics may be an effective strategy in sustainable pig production. The objective of this experiment was to examine the effects of Lactobacillus fermentum (LF) on nursery pig performance. Weaned pigs (n = 70; average initial BW 6.464 kg) were randomly allotted to 1 of 3 treatments, forming 6 replicates per treatment. Treatments included: 1) pigs fed a standard nursery diet (NRC 2012); CTL; 2) pigs fed CTL with the addition of 10^10 CFU LF per day for phase 1 (wk 2 and 3; LF1); and 3) pigs fed CTL with the addition of 10^10 CFU LF per day for phase 1 and phase 2 (wk 2 thru 5). A common diet was fed during adaptation (wk 1) and during a wash out phase (wk 6). Individual piglet BW were recorded weekly along with pen feed disappearance. No differences were observed in BW by the end of phase 1; at the end of phase 2 the pigs fed LF had a lower BW than the others (19.38, 19.22, 17.3 kg; P = 0.031). This was associated with a reduced feed efficiency seen in week 5 (0.679, 0.656, 0.445; P = 0.0404). However, no differences (P > 0.10) were observed in BW of the pigs throughout the trial and final BW were 24.15, 24.45, 24.3 kg. No differences were observed in ADFI between treatments (ADFI Phase 1: 0.359, 0.366, 0.353 kg/d;P = 0.965; Phase 2: 0.906, 0.896, 0.843 kg/d; P = 0.578; Phase 3: 1.183, 1.227, 1.196 kg; P = 0.920). Results suggest that pigs fed diets supplemented with Lactobacillus fermentum performed similar to pigs fed a conventional diet.